The neural basis of flashback formation: the impact of viewing trauma. - Bourne, C; Mackay, C; Holmes, E (2013)
BACKGROUND: Psychological traumatic events, such as war or road traffic accidents, are widespread. A small but significant proportion of survivors develop post-traumatic stress disorder (PTSD). Distressing, sensory-based involuntary memories of trauma (henceforth 'flashbacks') are the hallmark symptom of PTSD. Understanding the development of flashbacks may aid their prevention. This work is the first to combine the trauma film paradigm (as an experimental analogue for flashback development) with neuroimaging to investigate the neural basis of flashback aetiology. We investigated the hypothesis that involuntary recall of trauma (flashback) is determined during the original event encoding. Method A total of 22 healthy volunteers viewed a traumatic film whilst undergoing functional magnetic resonance imaging (fMRI). They kept a 1-week diary to record flashbacks to specific film scenes. Using a novel prospective fMRI design, we compared brain activation for those film scenes that subsequently induced flashbacks with both non-traumatic control scenes and scenes with traumatic content that did not elicit flashbacks ('potentials'). RESULTS: Encoding of scenes that later caused flashbacks was associated with widespread increases in activation, including in the amygdala, striatum, rostral anterior cingulate cortex, thalamus and ventral occipital cortex. The left inferior frontal gyrus and bilateral middle temporal gyrus also exhibited increased activation but only relative to 'potentials'. Thus, these latter regions appeared to distinguish between traumatic content that subsequently flashed back and comparable content that did not. CONCLUSIONS: Results provide the first prospective evidence that the brain behaves differently whilst experiencing emotional events that will subsequently become involuntary memories - flashbacks. Understanding the neural basis of analogue flashback memory formation may aid the development of treatment interventions for this PTSD feature.